PARP-dependent and NAT10-independent acetylation of N4-cytidine in RNA appears in UV-damaged chromatin - Svobodová Kovaříková, Alena; Stixová, Lenka; Kovařík, Aleš; Bártová, Eva (Epigenetics & chromatin, 2023)
RNA modifications have been known for many years, but their function has not been fully elucidated yet. For instance, the regulatory role of acetylation on N4-cytidine (ac4C) in RNA can be explored not only in terms of RNA stability and mRNA translation but also in DNA repair. Here, we observe a high level of ac4C RNA at DNA lesions in interphase cells and irradiated cells in telophase. Ac4C RNA appears in the damaged genome from 2 to 45 min after microirradiation. However, RNA cytidine acetyltransferase NAT10 did not accumulate to damaged sites, and NAT10 depletion did not affect the pronounced recruitment of ac4C RNA to DNA lesions. This process was not dependent on the G1, S, and G2 cell cycle phases. In addition, we observed that the PARP inhibitor, olaparib, prevents the recruitment of ac4C RNA to damaged chromatin. Our data imply that the acetylation of N4-cytidine, especially in small RNAs, has an important role in mediating DNA damage repair. Ac4C RNA likely causes de-condensation of chromatin in the vicinity of DNA lesions, making it accessible for other DNA repair factors involved in the DNA damage response. Alternatively, RNA modifications, including ac4C, could be direct markers of damaged RNAs.
Keywords: RNA; cytidin; Poly(ADP-ribose) Polymerase Inhibitors; acetylace; Cytidine; Acetylation; Chromatin; PARP inhibitory; chromatin